The Influence of Accountability and Transparency on The Quality of GMIT's Financial Reports in Kupang City - Linda Lomi Ga; Sarlin Paleina Nawa Pau; Maria Prudensiana Leda Muga (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
Church religious organizations need to pay attention to their financial reports as accountability so that users of these financial reports can understand the extent of the organization's financial condition. The church also needs to implement good financial management to produce accurate information. Accountability and transparency in the church as a non-profit organization is urgently needed, through accountability presented in quality financial reports, resource providers can ensure that the resources provided are used properly in church ministry to church congregations.How to collect data in this study is to use a questionnaire (questionnaire). Data analysis method in this study the method used is Ordinary Least Square Regression. The data was collected and processed using Descriptive Statistical Testing and Hypothesis Testing.The results of this study are the significance value of Accountability (X1) is the prob value. T-count of 0.008 <0.5 states that H1 is accepted which shows that the more accountable the accountability for financial reports made by the church, the quality of the GMIT church's financial reports in the Kupang city class is increasing. The results of this study are the significance value of Transparency (X2) is the prob value. T-count of 0.010 <0.5 states H2 is accepted indicating that the more transparent a church is in managing financial reports, the quality of the GMIT church's financial reports in Kupang City will increase.